2017
DOI: 10.18291/njwls.v7i3.97093
|View full text |Cite
|
Sign up to set email alerts
|

Between Money and Love: Work-family Conflict Among Swedish Low-income Single Mothers

Abstract: KeywoRds Control over work / economic resources / low-income and working-class Swedish single mothers / relative deprivation / structural ambivalence / work-family reconciliation Introduction It has been noted that the kinds of state support that single mothers receive can be used as a measure of the position of women more generally (Hobson, 1994, p. 176). The Nordic countries, where family policies emphasize both gender equality and equality in children's living conditions regardless of family form, are frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 35 publications
0
14
0
10
Order By: Relevance
“…Compared with all other family trajectories, women who spend a considerable time as a single mother may experience the greatest need to provide. We expect that single mothers will be the least driven by normative expectations toward motherhood: because they simply need to care and provide simultaneously, they cannot afford to lower their time investment in labor market activity (Roman 2017). However, single mothers could have great difficulties reconciling work and family because they carry the childcare burden on their own.…”
Section: Deviations From the Traditional Family Trajectorymentioning
confidence: 99%
“…Compared with all other family trajectories, women who spend a considerable time as a single mother may experience the greatest need to provide. We expect that single mothers will be the least driven by normative expectations toward motherhood: because they simply need to care and provide simultaneously, they cannot afford to lower their time investment in labor market activity (Roman 2017). However, single mothers could have great difficulties reconciling work and family because they carry the childcare burden on their own.…”
Section: Deviations From the Traditional Family Trajectorymentioning
confidence: 99%
“…For example, they may face lower income, no so cial support or benefits, low self-esteem, less personal satisfaction, and more tremendous time pressures (Knoef & van Ours, 2016). One of the main problems single working mothers face is wage discrimination and, as a result, economic insufficiency (Roman, 2017). In addition to wage discrimination within the same sector or even in the same organization, women's labor force is also concentrated in low-paying and labor-intensive industries such as textile or ready-wear (Kabasakal et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Baxter and Alexander () found that, in isolation from other factors, Australian single mothers report more WFC than coupled mothers. Single mothers' high levels of WFC may result from having to solely and with limited resources manage responsibilities (Alsarve, ; Roman, ; Son & Bauer, ) that are shared by two individuals in couples. In the absence of a partner, single mothers' total workload—combining work, domestic, and childcare responsibilities—places heavy demands on their family life, particularly compared with two‐parent families, as shown by previous studies from the three countries we examine in the present study (Bakker & Karsten, ; Kinnunen, Malinen, & Laitinen, ; Millar, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Whereas so‐called tag‐team parenting as a childcare‐related strategy can help to reduce coupled mothers' family workload and ensuring that the child receives parental care (see Mills & Täht, ; Murtorinne‐Lahtinen et al, ), single mothers navigate work and family responsibilities without a resident partner. Indeed, qualitative studies conducted in Europe (e.g., Alsarve, ; Roman, ) suggest that nonstandard work hours create major difficulties and pressures, particularly for single mothers in combining work and family life. Thus, we expect that the positive association between the amount of nonstandard work hours and WFC is stronger for single than coupled mothers because nonstandard work hours are unlikely to reduce single mothers' total family‐related workload for which the mother is solely and with more limited resources responsible for, compared with families with two parents (Hypothesis 2b).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation